Recycling of heavy metals and modification of biochar derived from Napier grass using HNO3. (15th September 2022) - Qin, Jianjun; Wang, Jing; Long, Jian; Huang, Jing; Tang, Shengshuang; Hou, Hongbo; Peng, Peiqin
Abstract: The disposal of biomass enriched with heavy metals (HMs) limits the application of phytoextraction. This study investigated the feasibility of obtaining K-rich fertilizer with low risk of HMs and biochar with good application prospect by extracting Napier grass biochar using 15% HNO3 and separating HMs from the filtrate using 40% KOH. In this study, Napier grass biochar produced at 500 °C showed better potential for utilization owing to its relatively low HM contents, high nutrient contents, and high yield. In fact, 61.26% Cd, 84.22% Zn, and more K were extracted from biochar when the pH was adjusted to 1 using 15% HNO3 . Then, Cd and Zn could be almost separated from the filtrate by adjusting the pH to 10 or more by adding 40% KOH. The Cd content in the biochar was reduced from a low risk level to a no-risk level, and the Zn content in the biochar was reduced from a medium risk level to a low risk level when the pH was adjusted to 1 and 2 by adding 15% HNO3 . The adsorption capacity of biochar to dyes was enhanced when the pH was adjusted to 1 using 15% HNO3 . The cation exchange mechanism endows the biochar with better potential for reuse (for methylene blue). This work provides a safe, efficient, and maneuverable resource allocation method. Graphical abstract: Image 1 Highlights: Napier grass biochar produced at 500 °C has good potential in resource utilization. ●HNO3 can realize simultaneous extraction and modification of Napier grass biochar. ●KOH can precipitate heavy metals in the leach liquor and supplement K element. ● q m of MB and KNR on modified biochar reached 101.13 and 13.23 mg g −1, respectively. ●The cation exchange mechanism endows the biochar with better potential for reuse.